2021
DOI: 10.1093/nar/gkab1120
|View full text |Cite
|
Sign up to set email alerts
|

Loss of full-length hnRNP R isoform impairs DNA damage response in motoneurons by inhibiting Yb1 recruitment to chromatin

Abstract: Neurons critically rely on the functions of RNA-binding proteins to maintain their polarity and resistance to neurotoxic stress. HnRNP R has a diverse range of post-transcriptional regulatory functions and is important for neuronal development by regulating axon growth. Hnrnpr pre-mRNA undergoes alternative splicing giving rise to a full-length protein and a shorter isoform lacking its N-terminal acidic domain. To investigate functions selectively associated with the full-length hnRNP R isoform, we generated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Heterogeneous nuclear ribonucleoproteins are often differentially expressed between tissues. For example, hnRNP R is enriched in the nervous system (Ghanawi et al , 2021). It is therefore possible that the relative amounts of individual 7SK/hnRNP complexes differ between distinct organs, contributing to cell‐type‐specific expression profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous nuclear ribonucleoproteins are often differentially expressed between tissues. For example, hnRNP R is enriched in the nervous system (Ghanawi et al , 2021). It is therefore possible that the relative amounts of individual 7SK/hnRNP complexes differ between distinct organs, contributing to cell‐type‐specific expression profiles.…”
Section: Discussionmentioning
confidence: 99%
“…hnRNP R is a heterogeneous nuclear ribonucleoprotein, which was found mostly in the nuclear and has important functions on transcription, splicing and mRNA transportation [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…hnRNP R is a heterogeneous nuclear ribonucleoprotein, which was found mostly in the nuclear and has important functions on transcription, splicing and mRNA transportation[46-49]. Besides that, hnRNP R can also be found in the cytosol and motoneuron axons[47, 48, 50], which plays important role in mRNA translation, mRNP transport and stress granule formation[51].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the level of expression of this family varies across cancers, implying that they play an important role in tumorigenesis. HNRNPR has recently shifted its focus to the mechanism of action in the nervous system [ 18 , 19 ]. Although it has been established as a proto-oncogene associated with gastric cancer (GC) [ 20 ], few studies have examined its role in other cancers.…”
Section: Introductionmentioning
confidence: 99%